Health Analysis of the Five Largest Banks in Indonesia during Global Uncertainty Using the RGEC Method: (Case Study on Bank Mandiri, BRI, BCA, BNI, and BTN for the Period 2020-2024) - Vika Diyah Ardiyanti; Arisha Putri Pradita (Politeknik Negeri Semarang, 2025)
Various countries are facing diverse and complex challenges in recent years. This certainly has an impact on the banking industry. This study aims to analyze the health level of the five banks with the largest assets in Indonesia in the period 2020 to 2024 using the RGEC method. The results of the study show that during the period 2020-2024, Bank Mandiri, BRI, and BCA received the predicate